2018
DOI: 10.1038/s41582-018-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin scavenging in intracranial bleeding: biology and clinical implications

Abstract: Haemoglobin is released into the CNS during the breakdown of red blood cells after intracranial bleeding. Extracellular free haemoglobin is directly neurotoxic. Haemoglobin scavenging mechanisms clear haemoglobin and reduce toxicity; these mechanisms include erythrophagocytosis, haptoglobin binding of haemoglobin, haemopexin binding of haem and haem oxygenase breakdown of haem. However, the capacity of these mechanisms is limited in the CNS, and they easily become overwhelmed. Targeting of haemoglobin toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 222 publications
(226 reference statements)
0
111
0
Order By: Relevance
“…The HP2 allele codes for an α 2 subunit that contains an extra cysteine residue compared to α 1 and is therefore able to make multiple disulfide bonds, resulting in several polymers of increasing size in HP2-1 heterozygotes and HP2-2 homozygotes. 10 Whether there is a functional difference between the proteins expressed by different HP genotypes is controversial and very much depends on which characteristic of Hp one considers. It is well established that Hp expression is influenced by genotype: HP1-1 > HP1-2 > HP2-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HP2 allele codes for an α 2 subunit that contains an extra cysteine residue compared to α 1 and is therefore able to make multiple disulfide bonds, resulting in several polymers of increasing size in HP2-1 heterozygotes and HP2-2 homozygotes. 10 Whether there is a functional difference between the proteins expressed by different HP genotypes is controversial and very much depends on which characteristic of Hp one considers. It is well established that Hp expression is influenced by genotype: HP1-1 > HP1-2 > HP2-2.…”
Section: Discussionmentioning
confidence: 99%
“…4 Some studies have suggested that haptoglobin (HP) genotype may also influence outcome, [5][6][7][8][9] but results are conflicting. 10 A recent meta-analysis found that the HP2 allele was associated with a worse short-term but not long-term outcome. 11 This meta-analysis had limitations, including small study sizes, heterogeneity in outcome classification, and inability to control for covariates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By understanding the relationship between ER stress in either activation of inhibition of other prominent factors of ICH including microglial activation [5,9], ROS production [6], proinflammatory cytokine release [11], and heme and iron release [13,14]; we will have a greater knowledge on the molecular mechanism involved in ICH induced secondary brain injury. In a traumatic brain injury (TBI) model, increased PERK phosphorylation resulted in the excessive release of interferon (IFN)-β through stimulator of interferon gene (STING) signaling pathway.…”
Section: Er Stress Components and Ich Therapeutic Strategiesmentioning
confidence: 99%
“…There are several naturally occurring protective pathways in the brain, guarding against the oxidative stress caused by blood toxicity, but these pathways get exhausted by ICH. Examples of such pathways include astrocytic release of haptoglobin (79)(80)(81)(82)(83) and haemopexin which scavenge haem and facilitate subsequent macrophage phagocytosis of these haem-scavenger complexes (79, 82).…”
Section: Oxidative Stressmentioning
confidence: 99%